(untitled) (Research, Society and Development, 2020)
Organic waste is derived from production processes, the amount of waste generated from two factories participating in this work reaches approximately 2000t / year, directly impacting the environment, making areas conducive to the development of insects and pests attracted by the discarded residual food. The cost used in the correct disposal of this waste, directing it to the local landfill is approximately R 150,000.00 / year. Considering the great nutritional value present in biomass, this work aimed to reuse these residues to produce a dog food. For this, a methodology was created to treat these biomasses, transforming them into co-products for commercialization. With this, a formulation was developed incorporating the by-products of olives, papayas and oranges, plus other essential ingredients for dog food, complying with the current legislation, resulting in a product with high added value. The developed feed used 38% of the residual biomass in its composition, and compromised, through the simulated study, all the material generated by the industries, being able to reduce a large part of the disposal expenses to the sanitary landfill. The generation of revenue from the sale of biomasses has subtracted the expenses with landfill disposal, making the process economically viable in addition to proposing a sustainable solution to the manufacturing process.